CORPORATE CRIMINAL LIABILITY CAUSED BY TENDER CONSPIRACY FOR GOODS/SERVICE PROCUREMENT THAT LEADS TO CORRUPTION - Ahmad Feri Tanjung; Ronald Hasudungan Sianturi; Rony Andre Christian Naldo (Universitas Labuhanbatu, 2024)
Tender conspiracy in goods/services procurement activities is prohibited. The legal fact is that in the procurement of goods/ services activities, there was a tender conspiracy which resulted in a criminal act of corruption. This research discusses tender conspiracies by corporations in goods/services procurement activities that lead to corruption. In this regard, this research is focused on examining corporate criminal liability due to tender conspiracies in goods/services procurement activities, which lead to criminal acts of corruption. This research is prescriptive analytical in nature, using normative juridical methods, using a statutory approach, concept approach and case approach. The type of data used is secondary data. The results of the research concluded that corporate criminal liability due to a tender conspiracy in the procurement of goods/services, which resulted in a criminal act of corruption, is that the corporation is subject to criminal liability with sanctions in the form of paying criminal fines, paying replacement money, and revoking the right to participate in government project auctions for 6 (six) months.Key Words: Corporations, Conspiracies, Corruption.